Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 20340034 species occurrences available in GBIF matching the query: { "Country" : [ "is Mexico" ] } The dataset includes 20340034 records from 2062 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0005506-171002173027117/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences